Search for heavy bottom-like quarks in 4.9 inverse femtobarns of $pp$ collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2208 authors); Hollar, Jonathan; Nayak, Aruna; Almeida, Nuno; Bargassa, Pedrame; David Tinoco Mendes, Andre; Faccioli, Pietro; Ferreira Parracho, Pedro Guilherme; Gallinaro, Michele; Musella, Pasquale; Seixas, Joao; Varela, Joao; et al. (My University, 2012)
Results are presented from a search for heavy bottom-like quarks, pair-produced in pp collisions at sqrt(s) = 7 TeV, undertaken with the CMS experiment at the LHC. The b' quarks are assumed to decay exclusively to tW. The b' anti-b' to t W(+) anti-t W(-) process can be identified by its distinctive signatures of three leptons or two leptons of same charge, and at least one b-quark jet. Using a data sample corresponding to an integrated luminosity of 4.9 inverse femtobarns, observed events are compared to the standard model background predictions, and the existence of b' quarks having masses below 611 GeV is excluded at 95% confidence level.